2021
DOI: 10.1128/aac.01482-20
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Community-Acquired Pneumonia Score To Improve Empiric Antibiotic Selection at an Academic Medical Center

Abstract: The 2019 American Thoracic Society and the Infectious Diseases Society of America Community-Acquired Pneumonia (CAP) Guidelines recommend drug resistant pathogens (DRP) be empirically covered if locally validated risk factors are present. This retrospective case-control validation study evaluated the performance of the Drug-Resistance in Pneumonia (DRIP) clinical prediction score. Two hundred 17 adult patients with ICD-10 pneumonia diagnosis, positive confirmed microbiologic data, and clinical signs and sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…By weighing this risk factor with a score of 14, patients growing Pseudomonas aeruginosa on any culture within 6 months prior to admission would automatically be identified as a case and would already pass the threshold of >11. This is similar to previous models and publications, which found that prior infection with a DRP on any culture within 1 year of admission was a risk factor for drug-resistant pneumonia ( 12 , 15 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…By weighing this risk factor with a score of 14, patients growing Pseudomonas aeruginosa on any culture within 6 months prior to admission would automatically be identified as a case and would already pass the threshold of >11. This is similar to previous models and publications, which found that prior infection with a DRP on any culture within 1 year of admission was a risk factor for drug-resistant pneumonia ( 12 , 15 ).…”
Section: Discussionsupporting
confidence: 92%
“…This is comparable to the AUROC of 0.77 in our validation cohort. Given that the previous study compared the different models derived from single institutions, the AUROC values of these models would likely be different if they were applied at our institution, as shown by others ( 15 ). In addition, the other models included DRPs collectively or MRSA and not specifically Pseudomonas aeruginosa , as was done in this analysis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An additional new method for improving empirical antibiotic selection is the community-acquired pneumonia score. This score provides a model of clinical data, thereby enabling the proper use of empirical antibiotics [17]. Implementation of an empiric therapy guide is important to minimize DRPs in the initial selection of antibiotics for pneumonia, as the causative organism and the patient's susceptibility to it are often unknown at the time of prescription.…”
Section: Drug-related Problems In Pneumonia 21 Improper Drug Selection and Dose Selectionmentioning
confidence: 99%
“…Therefore, a new method being considered for improving empirical antibiotic selection is the community-acquired pneumonia score. This score can be used in a prediction model of clinical data, enabling more accurate application of empirical antibiotics [17]. In addition, many intervention tools need to be applied, such as antibiotic management programs, biomarkers, and computerized physician order entries (CPOE), to ensure the effectiveness and safety of guideline compliance.…”
Section: Introductionmentioning
confidence: 99%